Decision Support System for Gaming Laptop Selection Using AHP - Vederico Pitsalitz Sabandar (Journal of Information Technology, Software Engineering and Computer Science, 2023)
This study aims to provide recommendations for gaming laptops using the AHP method with criteria for Hardware used, Graphics Card, Design, Cooling System, Reliability, Connectivity, Price, so that it becomes a solution for gamers in choosing the right laptop for gaming. The decision support system for gaming laptop selection recommendations developed is implemented using the Analytical Hierarchy Process (AHP) method. Where the AHP method can describe complex multi-factor or multi-criteria problems into a hierarchy, then the importance of each variable is given a subjective numerical value to be compared with other variables through a paired comparison matrix. Based on the assessment results using the AHP method, a recommendation for choosing the first gaming laptop by Dell Gaming G15 with a value of 0.806, the second model recommendation was obtained by Acer Nitro with a value of 0.5745, the third model recommendation was obtained by MSI Bravo 15 B5DD with a value of 0.524.